2021
DOI: 10.4314/ijbcs.v15i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an UV-Visible spectrophotometry assay method for the determination of chlorpheniramine maleate tablets without prior extraction

Abstract: Methods proposed by pharmacopeias to check the quality of chlorpheniramine maleate tablets are multi steps methods which involve extraction and present issues with repeatability. An alternative method is proposed with a sensitive, reliable, simple and rapid UV-VISIBLE spectrophotometry method developed for the determination without extraction of chlorpheniramine maleate in tablets. The method was validated using the accuracy profile approach with an accuracy ranging from 99.70 to 100.46%. Analysis was done usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This process is complicated to operate and requires costly chiral reagents and a longer reaction time with tedious workup (Nilesh, 2016). Thus, this study supports the synthesis of drugs as also reported in other studies (Bamba et al, 2021;Samuel and Adekunle, 2021;Kouamé et al, 2021;Chawe et al, 2021).…”
Section: Introductionsupporting
confidence: 92%
“…This process is complicated to operate and requires costly chiral reagents and a longer reaction time with tedious workup (Nilesh, 2016). Thus, this study supports the synthesis of drugs as also reported in other studies (Bamba et al, 2021;Samuel and Adekunle, 2021;Kouamé et al, 2021;Chawe et al, 2021).…”
Section: Introductionsupporting
confidence: 92%